Combining ability For shade Tolerence And Yield In Greengram Grown Under Coconuts - Preeta Liz Korah (Department of Plant Breeding and Genetics, College of Agriculture, 2001)
The current research programme on "Combining ability for shade tolerance and yield in greengram (Vigna radiata (L.) Wilczek) grown under coconuts" was carried out at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during 1998-2000. The objectives were estimation of gene action, combining ability effects of parents and hybrids and heterosis. The experimental material consisted of five lines, three testers and their fifteen hybrids. Analysis of variance revealed significant differences among the genotypes for all the eleven characters subjected to statistical analysis except height of plants and shade intensity. The genotypes L3 (MGG. 314), Ls (LGG. 460) and T3 (CO.2» were superior in mean performance for yield and most of the yield attributes. The hybrids Ls x T 2 (LGG. 460 x Pusa baisakhii and L1 x T3 (IIPRM.3 x CO.2) were superior in mean performance for yield, pod characters, photosynthetic efficiency and tolerance to pod bug infestation. Non-additive gene action predominated for all the nine characters showing significant differences among the treatments. Ls (LGG. 460) and T 2 (Pusa baisakhi) were the best general combiners for yield and